Pengaruh Daun Tapak Kambing (Ipomoae pes-caprae) Terhadap Konsentrasi Spermatozoa Tikus Putih (Rattus norvegicus) - Kaspul Kaspul (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2019)
Reproductive continuity is an important problem for humans and animals, but sometimes reproductive disorders occur which results in decreased reproductive capacity. Goat’s foot creeper leaves have active compounds that act as antioxidants. Antioxidant compounds can maintain reproductive function. This study aims to determine the effect of Goat’s foot creeper leaves on the spermatozoa concentration of white rats. Twenty white rats male (4-week-old) were treated with a completely randomized trial design. There were 4 treatment groups with 5 replications: (1) no treatment; (2) treatment with 750 mg goat’s foot creeper infusion per day; (3) treatment with 1500 mggfoot creeper leaves per day. All treatment groups were administered for 30 days orally. The results showed an increase in spermatozoa concentration of white rats.